Exploring the Ways Arabic as a Foreign Language (AFL) Teachers Target Students’ Critical Thinking - Nfissi, Abdelhamid; Elmzandi, Jaouhara; Laayadi, Soukaina (Pascasarjana IAIN Kudus, 2023)
Bloom’s taxonomy was created in 1956 by the educational psychologist Dr. Benjamin Bloom. It was created to promote higher-order thinking skills in the field of education, such as analyzing and evaluating concepts, procedures, and principles, rather than just retrieving facts. As a result, language teachers have access to varied ways to trigger and prompt students’ critical thinking by targeting their higher-order thinking skills. This qualitative research project explores how Moroccan AFL (Arabic as a Foreign Language) teachers target students’ critical thinking. This project focuses on the extent to which Moroccan AFL teachers trigger learners’ higher-order thinking skills, as well as the ways they target them. The research involved the observation of two lessons in a center of teaching Arabic as a foreign language. Three themes emerged from the data and were analysed: First, adopting the role of critical thinking, namely the role of a guide and mediator, not as a teacher of knowledge. Second, using two ways of motivation: positive comments and repeating students' answers. Third, implement activities and questions that help students not to take things for granted. Mengeksplorasi Cara Guru Pelajaran Arab sebagai Bahasa Asing (AFL) Menargetkan Pemikiran Kritis Siswa.Taksonomi Bloom yang diciptakan pada tahun 1956 Benjamin Bloom, psikolog pendidikan, bertujuan untuk mempromosikan keterampilan berpikir tingkat tinggi di bidang pendidikan, seperti menganalisis dan mengevaluasi konsep, prosedur, dan prinsip, bukan hanya mengambil fakta. Akibatnya, guru bahasa memiliki akses ke pelbagai cara untuk memicu dan mendorong pemikiran kritis siswa dengan menargetkan keterampilan berpikir tingkat tinggi mereka. Penelitian kualitatif ini mengeksplorasi bagaimana guru pelajaran Arab sebagai Bahasa Asing (AFL) Maroko menargetkan pemikiran kritis siswa, sehingga penelitian ini terfokus pada sejauh mana guru AFL Maroko memicu keterampilan berpikir tingkat tinggi peserta didik, serta cara mereka menargetkannya. Penelitian ini melibatkan observasi terhadap dua pelajaran di pusat pengajaran bahasa Arab sebagai bahasa asing. Penelitian ini menunjukkan cara seorang guru AFL Maroko menargetkan pemikiran kritis siswa; Pertama, mengadopsi peran berpikir kritis, yaitu peran sebagai pembimbing dan mediator, bukan sebagai guru sumber ilmu. Kedua, menggunakan dua cara motivasi, yaitu penggunaan komentar positif dan pengulangan jawaban peserta didik. Ketiga, menerapkan aktivitas dan pertanyaan yang membantu siswa untuk tidak menerima begitu saja.